3D analysis and grading of calcifications from ex vivo human meniscus. Issue 4 (April 2023) - Hellberg, I.; Karjalainen, V.-P.; Finnilä, M.A.J.; Jonsson, E.; Turkiewicz, A.; Önnerfjord, P.; Hughes, V.; Tjörnstrand, J.; Englund, M.; Saarakkala, S.
Summary: Objective: Meniscal calcifications are associated with the pathogenesis of knee osteoarthritis (OA). We propose a micro-computed tomography (μCT) based 3D analysis of meniscal calcifications ex vivo, including a new grading system. Method: Human medial and lateral menisci were obtained from 10 patients having total knee replacement for medial compartment OA and 10 deceased donors without knee OA (healthy references). The samples were fixed; one subsection was imaged with μCT, and the adjacent tissue was processed for histological evaluation. Calcifications were examined from the reconstructed 3D μCT images, and a new grading system was developed. To validate the grading system, meniscal calcification volumes (CVM ) were quantitatively analyzed and compared between the calcification grades. Furthermore, we estimated the relationship between histopathological degeneration and the calcification severity. Results: 3D μCT images depict calcifications in every sample, including diminutive calcifications that are not visible in histology. In the new grading system, starting from grade 2, each grade results in a CVM that is 20.3 times higher (95% CI 13.3–30.5) than in the previous grade. However, there was no apparent difference in CVM between grades 1 and 2. The calcification grades appear to increase with the increasing histopathological degeneration, although histopathological degeneration is also observed with small calcification grades. Conclusions: 3D μCT grading of meniscal calcifications is feasible. Interestingly, it seems that there are two patterns of degeneration in the menisci of our sample set: 1) with diminutive calcifications (calcification grades 1–2), and 2) with large to widespread calcifications (calcification grades 3–5).